ANALISIS KEPUASAN PELANGGAN KAHA TOUR AND TRAVEL ATAS PELAKSANAAN PELAYANAN PENJUALAN VOUCHER HOTEL DI TERMINAL 1 BANDAR UDARA SOEKARNO-HATTA TANGERANG BANTEN - Metha Dwi Apriyani; Ikeu Hikmawati (Bussman Journal : Indonesian Journal of Business and Management, 2021)
As a hotel voucher provider company that is actually engaged in hotel reservation services, Kaha Tour and Travel requires personnel (officers) to serve customers (guests) who need hotel voucher services. The implementation of services in the field of hotel voucher provision services is a direct service provided to customers (guests) so that customers (guests) understand and determine the demand for hotel voucher service products needed. Service activities are very important, because they create a very close and beneficial relationship for both the company and customers (guests). To measure the level of customer satisfaction with the Kaha Tour and Travel hotel voucher sales service carried out at Terminal 2 of Soekarno-Hatta International Airport, five indicators are used, namely reliability, responsiveness, confidence, empathy and tangibility which are implemented through a questionnaire as a data collection tool